Comparative Study of Economical Design Aspect of cable stayed Bridge with concrete , Steel, and prestressed deck girder using sap software - priyanka Rajput ,Nikita Thora,Monika Pagare, Raj Joshi (International Journal of Advanced Science and Technology, 2020)
Integrated circuits are in demand to be invetigated for its economical performance. Therefore, it is vialbe to experiment on ternary based operations[7]. A ternary half adder based on ternary multiplexer and logic primitives is proposed and its performance is analyzed in detail. This proposed ternary half is sensibly designed with the simplified expressions using the ternary k-map. The combinational logic blocks for the SUM and CARRY are designed, verified, constructed and simulated with Tanner EDA (130nm) at 1.2 V In this project the comparative study of cable stayed bridge is done using SAP2000 software and in this project we change the material of deck girder of bridges and comparison was done on the basis of shear force, bending moment, torsion, bending stress of girders with concrete and steel and prestressed girder of same span and same loading conditions and from the analysis we conclude about the most efficient girder we make on same span and loading conditions and we conclude that steel girders are more efficient than prestressed and concrete deck girders for the same span and loading conditions which we analyze through sap software